2018
DOI: 10.1177/0333102418804155
|View full text |Cite
|
Sign up to set email alerts
|

Self-perceived attention deficit and hyperactivity symptom levels and risk of non-migraine and migraine headaches among university students: A cross-sectional study

Abstract: Objectives The aim was to evaluate the association of self-perceived levels of attention deficit and hyperactivity symptoms with non-migraine and migraine headaches among university students. We also evaluated their association with migraine aura. Methods Study subjects were all participants in the internet-based Students Health Research Enterprise. Scores were built to evaluate global attention and hyperactivity symptom levels, self-perceived attention deficit levels and self-perceived hyperactivity symptom l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 29 publications
1
21
0
Order By: Relevance
“…In the visual modality, migraineurs were also found to present a heightened involuntary attentional orienting, a decreased ability to suppress unattended stimuli in the periphery, and abnormalities in top-down attentional processes (Mickleborough et al, 2011a). This is corroborated by reports of self-perceived attentional difficulties by migraineurs (Carpenet et al, 2019;Lévêque et al, 2020;Sacks, 1992). Furthermore, some clinic-based studies using neurophysiological tests revealed that migraine had a moderate effect on attentional performances during the interictal period (reviewed in Vuralli et al, 2018).…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…In the visual modality, migraineurs were also found to present a heightened involuntary attentional orienting, a decreased ability to suppress unattended stimuli in the periphery, and abnormalities in top-down attentional processes (Mickleborough et al, 2011a). This is corroborated by reports of self-perceived attentional difficulties by migraineurs (Carpenet et al, 2019;Lévêque et al, 2020;Sacks, 1992). Furthermore, some clinic-based studies using neurophysiological tests revealed that migraine had a moderate effect on attentional performances during the interictal period (reviewed in Vuralli et al, 2018).…”
Section: Introductionmentioning
confidence: 81%
“…This is quite consistent with anecdotal reports from migraineurs where they mention being easily distracted by their environment (Sacks, 1992). Migraineurs report higher self-perceived levels of attention difficulty than healthy controls (Carpenet et al, 2019;Lévêque et al, 2020). It is noteworthy that there exists a comorbidity of migraine with attention deficit and hyperactivity disorder (ADHD) (Fasmer et al, 2012;Paolino et al, 2015;Salem et al, 2017).…”
Section: Attention Dysfunction In Migrainementioning
confidence: 99%
“…Migraine has been associated with attentional abnormalities through subjective reports [15,52,78], neuropsychological tests [89,92], or EEG and event-related potentials (ERPs) studies [65].…”
Section: Discussionmentioning
confidence: 99%
“…Migraine has been associated with attentional abnormalities through subjective reports [15,52,78], neuropsychological tests [89,92], or EEG and event-related potentials (ERPs) studies [65]. However, little is known on the functional role of brain oscillations in the disruption of attention in migraine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation